High-power audio amplifier construction manual : 50 to 500 watts for the audio perfectionist - Slone, G. Randy (McGraw-Hill, 1999)
Fundamentals of high-power audio amplifiers - Misinformation in audio - Basic of audio power amplifiers - Input stage configurations and analyses - Voltage amplifier stage: configurations and analysis - Output stages: configurations, classes and device types - Stability, distortion and performance - Amplifier and loudspeaker protection methods - Audio amplifier power supplies and construction - Building the optimum audio power amplifier - Audi amplifier cookbook designs and discussions - Construction techniques and considerations - Power amplifier diagnostic equipment and testing procedures - Appendices.